The Influence of Reputation, Legality, and Credibility of Umrah Travel Agencies on the Trust of Pilgrims in Tegal City - Makhbub Syafiq Sobirin; Abdul Rozaq (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
The rapid growth of the Umrah pilgrimage industry in Indonesia after the Covid-19 pandemic was followed by an increase in the number of Umrah travel agencies, which presented new challenges related to pilgrim trust. This condition requires Umrah agencies to not only fulfill administrative aspects, but also build a strong reputation and credibility in the eyes of the public. This study aims to analyze the influence of the reputation, legality, and credibility of Umrah agencies on pilgrim trust in Tegal City. The study used a quantitative approach with a multiple regression analysis method. Data were obtained from 120 Umrah pilgrim respondents from five Umrah agencies verified by the Ministry of Religious Affairs of Tegal City through a Likert-scale questionnaire. Data analysis was performed using Google Colab. The results of the classical assumption test showed that the data met the Best Linear Unbiased Estimator (BLUE) criteria, with a Shapiro–Wilk normality test value of p = 0.1378, a maximum VIF value of 4.881, and a Breusch–Pagan heteroscedasticity test with p = 0.1171. Simultaneously, reputation, legality, and credibility significantly influence congregational trust (F = 213.3; p < 0.001). The adjusted R² value of 0.843 indicates that 84.3% of the variation in congregational trust can be explained by the model. Partially, reputation (β = 0.4253; p < 0.001) and credibility (β = 0.6009; p < 0.001) have a positive and significant effect, while legality has no significant effect (β = −0.0198; p = 0.775). This finding confirms that credibility and reputation are dominant factors in shaping congregational trust, while legality is perceived as a minimum requirement.